What Does Sustained Desistance from Violent Extremism Entail: A Proposed Theory of Change and Policy Implications - Cherney, Adrian (Terrorism and political violence, 2024)
While much is known about factors associated with deradicalisation and disengagement from violent extremism and terrorism, the underlying mechanisms at play have been under theorised. Literature on criminal desistance has a lot to offer in understanding the process of exiting from extremism, particularly in how it proceeds, the mechanisms at play and why it may or may not be sustained—what we term as the sustainability problem. We draw on criminal desistance scholarship to theoretically unpack the change processes underpinning desistance from extremism and why it is a challenging process for individuals. We propose a theory of cognitive transformation and explore the role of agentic change and external influences on the sustainability of desistance. We link our proposed theory of change to practical implications relating to the role of formal agents and how desistance from extremism can be supported, undermined, and assessed as authentic. Limitations with the theory of change are considered, as well directions for future research.